Carcinoid tumour of the cervix. Issue 619 (May 1977) - Daw, E.
Abstract : A case of non-metastatic carcinoid tumour of the cervix is described from a patient without the carcinoid syndrome. The rarity of carcinoid tumour involving gynaecological structures other than the ovaries is discussed and a bried review of carcinoid disease presented.